GROUND SURFACE BREAKS PRODUCED BY AN EARTHQUAKE AND VOLCANIC ERUPTIONS IN THE KARYMSKY VOLCANIC CENTER ON JANUARY 1-2, 1996 - Leonov V.L. (My University, 1998)
This paper presents the first results of an investigation of the ground-surface ruptures caused by a magnitude 7.0 earthquake and eruptions in the Karymsky volcanic center over the period January 1-2, 1996. The propagation and structure of the ruptures, the character of displacements, and the structural setting are discussed.